Anatomy and morphology character of five Indonesian banana cultivars (Musa spp.) of different ploidy level - ISSIREP SUMARDI; MERA WULANDARI (Biodiversitas Journal of Biological Diversity, 2010)
Sumardi I, Wulandari M (2011) Anatomy and morphology character of five Indonesian banana cultivars (Musa spp.) of different ploidy level. Biodiversitas 12: 167-175. In Indonesia there are many cultivars of banana, and some of them produce edible fruits. Beside their morphology, the character which necessary as a tool for classification is anatomical character. The aim of this research were to describe the anatomical character and morphology of fives Indonesian banana cultivars based on their level of ploidy. The cultivars were collected from Banana Germplasm Plantation, Yogyakarta District, Indonesia. The samples of roots, rhizome, and leaf were collected from five banana cultivars i.e.: Musa acuminata cv Penjalin, M. balbisiana cv Kluthuk warangan, M. acuminata cv Ambon warangan, M. paradisiaca cv Raja nangka, and M. paradisiaca cv Kluthuk susu. For anatomy observation samples were prepared using paraffin method, stained with 1% safranin in 70% ethanol. To observe the structure of stomata and epidermis surface, slide were prepared using modification of whole mount method. Slides were observed using Olympus BHB microscope completed with Olympus camera BM-10A. Stem and leaf morphology character of diploid level (AA and BB genome) is different with triploid level (AAA, AAB, and ABB genome). Anatomy and morphology character of root and rhizome of banana in diploid level (AA and BB genome) and triploid level (AAA, AAB, and ABB genome) is quite similar. Distribution of stomata is found in leaf and pseudostem. Stomata is found in adaxial and abaxial epidermis layer. The size of guard cells in triploid cultivars was longer than that diploid cultivars. The root composed of epidermis layer, cortex and cylinder vascular of five cultivar’s root show anomalous structure. Rhizome consist of peripheric and centre zone. Anatomically, this was no differences in the rhizome structure among five banana cultivars. The row of vascular bundles acts as demarcation area between peripheric and central zone. In the cultivar with BB genome (diploid) and ABB genome (triploid) the row of vascular bundle was not found. The differences of leaf anatomy were base on: size and number of stomata distribution, number of subsidiary cells, number of hypodermal layers, structure and number of parenchyma palisade, size of airspace in petiole and mesophyll and the vascular bundle structure.Key words: anatomical character, morphology, banana cultivar, ploidy level